Transformasi Pendidikan Islam di Era Digital: Analisis Sekularisasi Terselubung dalam Islamic EdTech di Indonesia - Ira Ariyanti; Wini Kurniadewi; Husni Thoyyar (Universitas Muhammadiyah Bandung, 2025)
The rapid development of information technology has accelerated the emergence of Islamic Education Technology (Islamic EdTech) as an innovation in Islamic education that provides wider access, improved effectiveness, and interactive learning experiences. However, its application faces ideological challenges, particularly the potential for hidden secularization through the separation of religious and general sciences, the adoption of Western pedagogical standards, and the dominance of digital algorithms. This study aims to analyze the potential secularization within Islamic EdTech in Indonesia by employing a qualitative descriptive method based on document analysis and in-depth interviews with teachers, platform developers, and academics. Data were thematically analyzed using NVivo software, supported by source and method triangulation to ensure validity. The findings indicate that although Islamic EdTech successfully enhances learning access and motivation among younger generations, there is a tendency toward reducing Islamic teachings to cognitive aspects, neutralizing religious terminology, and shaping business-oriented platforms that treat Islamic values as mere symbolic labels. Therefore, content curation involving scholars, collaboration with Islamic educational institutions, and the establishment of Sharia-based ethical guidelines for technology use, including artificial intelligence, are essential. With these strategic measures, Islamic EdTech has the potential not only to modernize Islamic learning but also to function as a medium of Islamization of knowledge while strengthening Islamic identity amid the challenges of educational globalization.